1993
DOI: 10.2466/pms.1993.76.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Endorphins and Mood States during Resistance Exercise

Abstract: Research examining the relationship between beta-endorphin immunoreactivity and affect has resulted in equivocal findings. To examine this relationship further, 10 male and 10 female college-age students participated in a controlled free-weight exercise session. Blood plasma samples were procured both prior to and following the exercise bout and beta-endorphin levels were determined by immunoassay. Analysis indicated that plasma beta-endorphin levels following exercise were significantly decreased from pre-exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Exercise improves autonomic dysfunction, heart rate variability, and inflammatory markers, and therefore it could potentially improve CHD outcome . In addition, exercise leads to release of endorphins that could improve mood and enhance the sense of well‐being . Endorphins could further improve physical function and exercise capacity in return, and thus lead to decrease in arterial stiffness and, hence, improved endothelial function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise improves autonomic dysfunction, heart rate variability, and inflammatory markers, and therefore it could potentially improve CHD outcome . In addition, exercise leads to release of endorphins that could improve mood and enhance the sense of well‐being . Endorphins could further improve physical function and exercise capacity in return, and thus lead to decrease in arterial stiffness and, hence, improved endothelial function .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 In addition, exercise leads to release of endorphins that could improve mood and enhance the sense of well-being. 42 Endorphins could further improve physical function and exercise capacity in return, and thus lead to decrease in arterial stiffness and, hence, improved endothelial 43 Improved endothelial function has shown to be associated with decreased risk of CHD. 44 Additionally, a recent meta-analysis highlighted that brain structural changes associated with depression, such as volumetric reduction of certain areas and loss of networks integrity in between, might be enhanced by exercise treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Thaxton used the CTR to assess exercise dependence. As well, Thaxton neither monitored nor controlled running intensity during her experiment, a factor that might have infiuenced scores on the various measures she employed (Pierce et al, 1993). Unfortunately, Thaxton did not describe the associations between her participants' self-ratings on exercise addiction and their CTR scores.…”
Section: Exercise Withdrawalmentioning
confidence: 98%
“…Pierce et al (1994) examined /3-endorphin levels in 10 male recreational weightlifters, and 10 female basketball players. McGowan et al (1993) reported that, the sample utilised by Pierce et al (1994) had also completed the Profile of Mood States (POMS: McNair et al, 1971) prior to and on completion of the exercise bout (at the same time as they had provided the blood sample). Pierce and his colleagues reported that the postexercise samples showed a significant reduction in serum levels of /?-endorphin, a finding which, they hypothesised, could refiect a change in psychological state, rather than a physiological response to exercise.…”
Section: The Possible Role Of Endogenous Opioids In Exercise Dependencementioning
confidence: 99%
“…9 However, not all physical training modalities present the same effects. [10][11][12] Recently, moderate and high-intensity exercises are gaining prominence, as they bring similar benefits to others and require a shorter time investment. 13 In the past few years, extreme conditioning training programs (ECT) became one of the most physical exercises searched by many people in Brazil.…”
Section: Introductionmentioning
confidence: 99%